Prognostic value of Bmi-1 oncoprotein expression in NSCLC patients: a tissue microarray study - Vrzalikova, Katerina; Skarda, Joseph; Ehrmann, Jiri; Murray, Paul G.; Fridman, Eduard; Kopolovic, Jury; Knizetova, Petra; Hajduch, Marian; Klein, Jiri; Kolek, Vitezslav; Radova, Lenka; Kolar, Zdenek (Journal of cancer research and clinical oncology, 2008)
Purpose Bmi-1 is a Polycomb group member which participates in many physiological processes as well as in a wide spectrum of cancers. The aim of this study was to investigate Bmi-1 expression in non-small cell lung cancer (NSCLC) in respect to clinicopathological features and therapeutic outcomes. Methods Immunohistochemical staining for Bmi-1 was performed on tissue microarrays (TMAs) constructed from 179 formalin-fixed and paraffin-embedded NSCLC samples (106 squamous, 58 adeno-, and 15 large cell carcinomas). Data were subject to statistical analysis by SPSS. Results Overall evaluation of all tumor cases showed that 20 (11.43%) were negative, 37 (21.14%) showed weak, 65 (37.14%) moderate and 57 (32.57%) strong nuclear positivity for Bmi-1. Statistical analysis of our data revealed that the expression of Bmi-1 was significantly higher in stage III ( P = 10 −6 ) and stage IV ( P = 10 −5 ) tumors compared to stages I and II tumors. The administration of adjuvant chemotherapy significantly increased DFS at stage I and II patients who did not express Bmi-1 when compared to their Bmi-1 positive counterparts ( P = 0.05). Conclusions Our results suggest that Bmi-1 is significantly associated with progression of NSCLC and might serve as a prognostic marker of adverse disease outcome.